Dying Care Nursing Intervention in the Institutional Care of End-of-Life Patients - Kisvetrová, Helena; Joanovič, Eva; Vévoda, Jiří; Školoudík, David (International journal of nursing knowledge, 2017)
PURPOSE: To determine the frequency of the Nursing Intervention Classification Dying Care activities performed by nurses with end-of-life (EOL) patients. METHODS: A cross-sectional, descriptive study using a structured questionnaire to determine the frequencies of Dying Care activities performed by 201 Czech nurses. FINDINGS: Nurses reported more frequent use of activities focused on the physical comfort of EOL patients. Significant relationships were found between frequencies in some activities and the nurses' education level, length of work experience, and the department type. CONCLUSIONS: Nurses reported infrequent use of communication activities with patients and relatives, which is related to the length of practice. CLINICAL RELEVANCE: It is necessary to focus on communication and psychosocial needs of EOL patients in both pregradual and lifelong nursing education. CÍL: Zjistit frekvenci aktivit NIC intervence Péče o umírající mezi českými sestry u pacientů v závěru života. METODY: Průřezová deskriptivní studie využívající strukturovaného dotazníku pro určení frekvence aktivit Péče o umírající prováděné 201 sestrou. VÝSLEDKY: Sestry u pacientů v závěru života častější využívají aktivity zaměřené na fyzický komfort. Významné vztahy byly nalezeny mezi frekvencí některých aktivit a úrovní vzdělání sester, délkou praxe a typem pracoviště. ZÁVĚRY: Sestry uváděly nepříliš časté používání komunikačních aktivit s pacienty a příbuznými, což souvisí s délkou jejich praxe. KLINICKÁ RELEVANCE: Je třeba se zaměřit na komunikaci a psychosociální potřeby pacientů v závěru života jak v pregraduálním tak celoživotním vzdělávání sester.
Keywords: terminally ill; end-of-life; průzkumy a dotazníky; Cross-Sectional Studies; Terminal Care; paliativní péče; průřezové studie; ošetřovatelská péče; Humans; Palliative Care; Dying care; nursing intervention; Surveys and Questionnaires; Nursing Care; lidé; péče o umírající